2x-4(x-3)=-9+5x-14

Simple and best practice solution for 2x-4(x-3)=-9+5x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4(x-3)=-9+5x-14 equation:


Simplifying
2x + -4(x + -3) = -9 + 5x + -14

Reorder the terms:
2x + -4(-3 + x) = -9 + 5x + -14
2x + (-3 * -4 + x * -4) = -9 + 5x + -14
2x + (12 + -4x) = -9 + 5x + -14

Reorder the terms:
12 + 2x + -4x = -9 + 5x + -14

Combine like terms: 2x + -4x = -2x
12 + -2x = -9 + 5x + -14

Reorder the terms:
12 + -2x = -9 + -14 + 5x

Combine like terms: -9 + -14 = -23
12 + -2x = -23 + 5x

Solving
12 + -2x = -23 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
12 + -2x + -5x = -23 + 5x + -5x

Combine like terms: -2x + -5x = -7x
12 + -7x = -23 + 5x + -5x

Combine like terms: 5x + -5x = 0
12 + -7x = -23 + 0
12 + -7x = -23

Add '-12' to each side of the equation.
12 + -12 + -7x = -23 + -12

Combine like terms: 12 + -12 = 0
0 + -7x = -23 + -12
-7x = -23 + -12

Combine like terms: -23 + -12 = -35
-7x = -35

Divide each side by '-7'.
x = 5

Simplifying
x = 5

See similar equations:

| 3b+12-5b=22 | | 0.07-0.06(5x+4)=0.06x+0.13 | | 4x+13=-7x-30 | | 4x^2-26-14= | | 32m+54m+22=0 | | 6x-4x+20=-16 | | 2+3v=-6v-16 | | 3x+20+2(4x+4)=2x | | 26-(4x-11)=5(x+7) | | -(5z+1)=18 | | 4x+8-3x=14 | | 6x^3=5x^2 | | 3x+5.2=2-5y | | x+5=x+0 | | -13+7=-h-7+7 | | 3x-15=17-x | | 3(5y+2)-y=(2y-3) | | x=23-(-11) | | 8-3x=3x+2 | | 66=9x-13-8x+29 | | x/8+6=-12 | | 23-(-11)= | | w+(-9)=-4 | | 3x-15=3x | | 8x=6x-14 | | 2x-3=32 | | 15=5x-3(x+7) | | 4x-6=10x | | 21+29x=42+22x | | 81k^2-49=0 | | -[4z-(12z+6)]=6+(7z+7) | | 8-2a=-12 |

Equations solver categories